“Burn the witch”: The impact of the fear of witchcraft on social cohesion in South Africa - Ally, Yaseen (PINS-Psychology in Society, 2024)
This paper explores beliefs about witchcraft in a sample of community members in South Africa with the aim of showing that the fear of bewitchment dislocates important linkages and networks between people. This is most evident in relation to the violent consequences associated with witchcraft, particularly affecting those who are accused. Interviews with community members in South Africa provide us with a context to understand the emotional response discourses that witchcraft opens. This allows comments on how witchcraft beliefs are fused with fear, which mobilises community members towards behaviour against those accused. As a consequence, violent behaviour becomes an acceptable outlet in coping with witchcraft accusations. It is argued that increased distrust amongst community members related to witchcraft leads to tension and interpersonal conflict, therefore breaking down networks essential to ensuring harmony.